The Effect Of Technological Disruption On The ASEAN Economic Community: An Regulatory Analysis Of Legal Education In Indonesia - Tejomurti, Kukuh; Hermawan, Sapto (Acta Law Journal, 2022)
The implementation of the provisions of the ASEAN Economic Community (MEA) and the influence of Artificial Intelligence (AI) in analyzing legal issues are essential points that must be considered by legal education in Indonesia. Soekarno thought that education is the main priority to be implemented because it is a determining factor for the development of humanity. There is no way to fix the downturn of the people other than to form an education rooted in humanity's values, principles, and goals. This article discusses the relevance of Soekarno's thoughts regarding the importance of education in facing the rapid development of society and how educators and the legal profession should respond to these developments. AI can not just have the idea to create the latest technological sophistication alone. However, it is necessary to consider its usefulness in the future regarding the concept of the AI system. Concerns arise when people may believe whether AI will reflect human values?